PD and M5S: The Italian alliance of convenience. The power of the status quo in a challenging economic context - Emanuele Caggiano; Paweł Tokarski (Stiftung Wissenschaft und Politik (SWP), 2019)
The attempt to provoke early elections in August 2019 by the leader of the League, Matteo Salvini, unexpectedly led to a pragmatic coalition of the Five-Star Movement (M5S) and the Democratic Party (PD) and the formation of a second government under Giuseppe Conte. This government operates in a fragile political equilibrium where a fear of early elections, which could pave the way for Matteo Salvini to power, is the main stabilising factor. The pragmatic political calculation of the PD and M5S supported by Matteo Renzi's new party "Italia Viva" may be enough to maintain the coalition for a certain time, but it will not generate any major growth incentives for Italy, which are crucial in maintaining the sustainability of public debt.
Keywords: 320